Mice that express human interleukin-8 have increased mobilization of immature myeloid cells, which exacerbates inflammation and accelerates colon carcinogenesis - Asfaha, S.; Dubeykovskiy, A.N.; Tomita, H.; Yang, X.; Stokes, S.; Shibata, W.; Friedman, R.A.; Friedman, R.A.; Dubeykovskaya, Z.A.; Muthupalani, S.; Ericksen, R.; Frucht, H.; et al.
Background Aims: Interleukin (IL)-8 has an important role in initiating inflammation in humans, attracting immune cells such as neutrophils through their receptors CXCR1 and CXCR2. IL-8 has been proposed to contribute to chronic inflammation and cancer. However, mice do not have the IL-8 gene, so human cancer cell lines and xenograft studies have been used to study the role of IL-8 in colon and gastric carcinogenesis. We generated mice that carry a bacterial artificial chromosome that encompasses the entire human IL-8 gene, including its regulatory elements (IL-8Tg mice). Methods: We studied the effects of IL-8 expression in APCmin+/- mice and IL-8Tg mice given azoxymethane and dextran sodium sulfate (DSS). We also examined the effects of IL-8 expression in gastric cancer in INS-GAS mice that overexpress gastrin and IL-8Tg mice infected with Helicobacter felis. Results: In IL-8Tg mice, expression of human IL-8 was controlled by its own regulatory elements, with virtually no messenger RNA or protein detectable under basal conditions. IL-8 was strongly up-regulated on systemic or local inflammatory stimulation, increasing mobilization of immature CD11b+Gr-1+ myeloid cells (IMCs)with thioglycolate-induced peritonitis, DSS-induced colitis, and H. felis-induced gastritis. IL-8 was increased in colorectal tumors from patients and IL-8Tg mice compared with nontumor tissues. IL-8Tg mice developed more tumors than wild-type mice following administration of azoxymethane and DSS. Expression of IL-8 increased tumorigenesis in APCmin+/- mice compared with APCmin+/- mice that lack IL-8; this was associated with increased numbers of IMCs and angiogenesis in the tumors. Conclusions: IL-8 contributes to gastrointestinal carcinogenesis by mobilizing IMCs and might be a therapeutic target for gastrointestinal cancers.
Keywords: COLON CANCER; GASTRIC CANCER; IMMUNE REGULATION; MOUSE MODEL